(untitled) (Ágora Journal, 2020)
The plebiscite or plebiscitary motion, launched in the municipality of São Borja / RS in 1888 had the objective of consulting the population if the possibility of a third reign starting in Brazil would be accepted. The proposal made by Aparício Mariense, influential politician of the Republican Party of that city had great repercussion in several journals. This article aims to analyze how the official newspaper of the Rio-Grandense Republican Party A Federação reported the fact during the period between January and March 1888. The analysis was carried out through the methodology of the Scheduling Hypothesis or Agenda Setting. The paper was developed with the following objectives: Contextualize how the Rio Grandense Republican Party started, as well as the São Borja Republican Party and how the politician Aparício Mariense stood out. Later on, how the press source became an important object of study for historiography, and finally, the Scheduling Hypothesis applied in articles directed to the plebiscite, what was the purpose of the publication of the articles and what are their results on the political agenda. Pointing out, as a result, the commitment of a press with a political bias in influencing the adhesion of the plebiscite of several municipalities in Rio Grande do Sul and in the state of São Paulo.